Interferon α in the treatment of polycythemia vera - Lengfelder, Eva; Berger, Ute; Hehlmann, Rüdiger (Annals of hematology, 2000)
(IFN) inhibits the growth of the abnormal clone in patients with myeloproliferative disorders, leading to a reduction of the clinical and laboratory signs of the pathologic myeloproliferation. The therapeutic efficacy of IFN in polycythemia vera (PV) is demonstrated by the summarized treatment results of 279 patients participating in 16 prospective nonrandomized studies and in three case reports. The initial IFN dose ranged from 3 to 35 million IU/week. In 82% of the patients the frequency of phlebotomies was reduced. In 50% a complete remission was achieved, defined as a stable hematocrit of 45% without concomitant phlebotomies. Reduction of splenomegaly was seen in 77% and control of pruritus in 81% of the patients. The median observation time of the studies was 13 months (ranging from 3 to 84 months). Individual cases were followed for up to 126 months. In 21% of the patients IFN was terminated, owing mostly to side effects. The selective suppression of the malignant clone by IFN was demonstrated by the induction of cytogenetic remissions in sporadic cases with a chromosomal marker and by the observation of unmaintained remissions that lasted up to 4.8 years. IFN has no known mutagenic or teratogenic effects. The data presently available demonstrate that IFN is an effective alternative to the present forms of treatment in PV. Controlled prospective studies are essential to clarify whether the favorable biologic properties are also reflected by a benefit in clinical course and survival, and whether IFN may reduce the rates of acute leukemia and myelofibrosis. A randomized study that compares IFN and hydroxyurea in patients with PV has recently been initiated by the Süddeutsche Hämoblastosegruppe (SHG) in Germany.
Gesehen am 19.05.2022